Kinetic Analysis of Bovine Factor VIII in the Hemophilic Dog - Gentry, Patricia A; Kirby, Edward P; Gentry, Rodney D (Thrombosis and Haemostasis, 1981)
Bovine factor VIII, which did not contain platelet aggregating factor activity, was infused into hemophilic dogs. Factor VIII procoagulant (VIII: C) levels in the dogs increased dramatically, then decreased in a biphasic manner. The half-life of the longest component was 3-7 hrs. The infusions were hemostatically effective and also caused a prolonged shortening of the activated partial thromboplastin time. These studies demonstrate that the platelet aggregating factor activity of bovine factor VIII is not essential for its maintenance in the circulation and that preparations lacking this activity may be clinically useful. When concentrates of partially purified factor VIII: C (essentially free of both platelet aggregating factor and factor VIII-related antigen) were infused, marked increases in VIII: C levels were also observed, but the half-life was significantly shorter (T1/2 of approximately 1 hr).
Keywords: Factor VIII; Factor VIII turnover; Bovine; Dog; Hemophilia